2022
DOI: 10.3390/bios12060409
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Device for Measurement of Exhaled Breath for the Detection of Obstructive Lung Disease

Abstract: Breath sensor technology can be used in medical diagnostics. This study aimed to build a device to measure the level of hydrogen sulfide, ammonia, acetone and alcohol in exhaled breath of patients as well as healthy individuals. The purpose was to determine the efficacy of these gases for detection of obstructive lung disease. This study was conducted on a total of 105 subjects, where 60 subjects were patients of obstructive lung disease and 45 subjects were healthy individuals. Patients were screened by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…From this view, the data transmission was effective when the distance between the measuring system and the Android device was up to 10 meters without obstacles as found also in [38]. This result shows that HC-05 module is more suitable for this portable spirometer, instead of using a local liquid crystal display (LCD) or universal serial bus (USB) connection as in [20], [22]. It can provide energy-efficient short-range wireless data transmission with good throughput between mobile phones and many biomedical devices [39], [40], such as in a portable vital sign monitoring system [41], low-cost portable electrocardiogram (ECG) monitoring systems [38], [42]- [44], and an electroencephalogram (EEG)-controlled system for disabled and elderly people [45].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…From this view, the data transmission was effective when the distance between the measuring system and the Android device was up to 10 meters without obstacles as found also in [38]. This result shows that HC-05 module is more suitable for this portable spirometer, instead of using a local liquid crystal display (LCD) or universal serial bus (USB) connection as in [20], [22]. It can provide energy-efficient short-range wireless data transmission with good throughput between mobile phones and many biomedical devices [39], [40], such as in a portable vital sign monitoring system [41], low-cost portable electrocardiogram (ECG) monitoring systems [38], [42]- [44], and an electroencephalogram (EEG)-controlled system for disabled and elderly people [45].…”
Section: Resultsmentioning
confidence: 67%
“…The MEMS flow sensors have been widely used in biomedical applications to measure air flow, especially respiratory flow [16]- [18]. Meanwhile, a device has been developed to measure the other respiratory values, such as forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) [19], and level of hydrogen sulfide, ammonia, acetone and alcohol in patients' exhaled breath [20]. Other studies have implemented the spirometer to detect asthma symptoms and COPDs providing effective treatment for the patients [21]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NH 3 concentration is an important factor in chronic lung diseases such as asthma. In 2022, Shahzad and co-workers measured the concentration of NH 3 in the EB of obstructive lung patients and healthy subjects . The obtained results showed a decrease in NH 3 concentration from 103.49 ppb for healthy subjects to 68.83 ppb for obstructive lung patients.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that it was higher in COPD patients without sputum eosinophilia [ 192 ]. Exhaled sulfide was lower in COPD patients compared to healthy subjects and correlated with airway obstruction in another study [ 193 ]. Other authors found that exhaled H 2 S was correlated with FeNO but not with sputum inflammatory cells in COPD [ 194 ].…”
Section: Exhaled Gaso-transmittersmentioning
confidence: 99%